Mental health and sleep disturbances in physically active adults during the COVID-19 lockdown in Norway: Does change in physical activity level matter? - Ernstsen, L.; Havnen, A. (Sleep Medicine, 2020)
Study objective: To assess mental health and sleep disturbances among physically active adults during the Norwegian lockdown caused by the coronavirus disease 2019 (COVID-19), and to investigate if change in physical activity (PA) level during the lockdown moderates the association between mental health and sleep disturbances. Methods: Members of a Norwegian fitness association were invited to fill out an online questionnaire including the Hospital Anxiety and Depression Scale (HADS), sleep disturbances and change in PA habits (decreased, unchanged, increased) during the COVID-19 lockdown from 12 March to 15 June 2020. Results: A sample of 1281 members aged 19-81 years were included (31% females; mean ± SD age 49 ± 11.5). Prevalence of anxiety and depressive symptoms was 9.0% and 4.4%, respectively. During the lockdown period, 13.8% reduced, 21.9% increased and 64.3% did not change PA level. In total 21.9% reported sleeping disturbances. Anxiety symptoms and depressive symptoms were statistically significantly associated with sleep disturbances. Change in PA did not influence the association between mental health and sleep. Conclusion: Compared to studies from the general population during the COVID-19 pandemic levels of anxiety and depressive symptoms were substantial lower in this Norwegian sample of relatively physically active adults. Anxiety and depressive symptoms were associated with sleep disturbances, but change in PA level during the COVID-19 lockdown did not influence the association between mental health and sleep disturbances.